2021
DOI: 10.1007/s11109-021-09749-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Politician’s Moral Violations on Voters' Moral Emotions

Abstract: Existing empirical research on voters’ responses to individual politicians’ moral transgressions pays limited attention to moral emotions, although moral emotions are an integral part of voters’ moral judgment. This study looks at U.S. voters’ discrete moral emotional responses to politician’s moral violations and examines how these discrete moral emotional responses are dependent on voters’ own moral principles and the extent to which they identify with a political party. We report on a 5 × 3 between-subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 44 publications
1
2
0
1
Order By: Relevance
“…This bolsters the notion that schadenfreude and sympathy are prominent intergroup emotions (Cikara & Fiske, 2013) and may play an important role in partisanship (e.g., Hibbing et al, 2014;Inbar et al, 2012). This finding also corroborates research showing that voters have divergent moral emotional responses (e.g., anger, contempt, disgust) to moral violations when they share party identity with a politician (Combs et al, 2009;Walter & Redlawsk, 2021). It is worth mentioning that differences in schadenfreude and sympathy by political affiliation may have been due to reporting bias.…”
Section: Discussionsupporting
confidence: 81%
“…This bolsters the notion that schadenfreude and sympathy are prominent intergroup emotions (Cikara & Fiske, 2013) and may play an important role in partisanship (e.g., Hibbing et al, 2014;Inbar et al, 2012). This finding also corroborates research showing that voters have divergent moral emotional responses (e.g., anger, contempt, disgust) to moral violations when they share party identity with a politician (Combs et al, 2009;Walter & Redlawsk, 2021). It is worth mentioning that differences in schadenfreude and sympathy by political affiliation may have been due to reporting bias.…”
Section: Discussionsupporting
confidence: 81%
“…Največje raziskovalne zlorabe ljudi v imenu politike so se skozi zgodovino srhljivo odražale skozi izvajanje eksperimentov z namenom sistematičnega uničevanja prvobitnih ljudstev v času kolonizacije ter vojn, pa vse do današnjih dni skozi neenake obravnave posameznikov in posameznih skupin ter skozi informacijsko manipuliranje z ljudmi (npr. Amon idr., 2012;Imhoff idr., 2012;Walter in Redlawsk, 2021). Prav tako pa so na konkretnih primerih raziskovanja, povezanega s politiko in človekovimi pravicami, poznani tudi primeri izginotij ali celo javnih likvidacij raziskovalcev in novinarjev, ki so na terenu zbrali podatke, za katere se je izkazalo, da niso ustrezali namenom politične propagande in pričakovanjem vladajoče politične elite.…”
Section: Makroprostor: Politične Institucije Vseh Treh Vej Oblasti Na...unclassified
“…However, because not every respondent in our survey had directly experienced the loss of program access, we designed our survey to capture both real and hypothetical emotional and behavioral responses to losing access. The usage of hypothetical scenarios is a widely used approach in psychology (e.g., Robinson & Clore, 2001), political psychology (e.g., Petersen et al, 2012; Walter & Redlawsk, 2021), and more recently public administration (Guul et al, 2021; Jilke & Tummers, 2018). Research has shown that hypothetical scenarios generally elicit responses that can be reproduced in non-hypothetical settings (Hainmueller et al, 2015; Robinson & Clore, 2001).…”
Section: Data Description and Measurementmentioning
confidence: 99%